Unique Clusters of Severe Acute Respiratory Syndrome Coronavirus 2 Causing a Large Coronavirus Disease 2019 Outbreak in Hong Kong. (5th August 2020) - To, Kelvin Kai-Wang; Chan, Wan-Mui; Ip, Jonathan Daniel; Chu, Allen Wing-Ho; Tam, Anthony Raymond; Liu, Raymond; Wu, Alan Ka-Lun; Lung, Kwok-Cheung; Tsang, Owen Tak-Yin; Lau, Daphne Pui-Ling; To, Wing-Kin; Kwan, Mike Yat-Wah; et al.
Abstract: After 2 months of relative quiescence, a large coronavirus disease 2019 outbreak occurred in Hong Kong in July 2020 after gradual relaxation of social distancing policy. Unique severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) phylogenetic clusters have been identified among locally acquired cases, with most genomes belonging to cluster HK1, which is phylogenetically related to SARS-CoV-2 reported overseas.